Tomographic assessment of bone changes in atrophic maxilla treated by split-crest technique and dental implants with platelet-rich fibrin and NanoBone® versus platelet-rich fibrin alone: Randomized controlled trial - Maged Anis; Ahmed Reda Abdelrahman; Rasha Attia; Amr Zahran (BMC, 2024)
Abstract Background This study evaluated the clinical benefits of adding NanoBone® with split-crest technique and simultaneous implant placement covered with platelet-rich fibrin membrane in horizontally deficient maxillary ridges in terms of crestal and horizontal bone changes and patient morbidity. Methods Forty patients indicated for maxillary ridge splitting and simultaneous implant placement were assigned randomly to the study groups: control group (Platelet Rich Fibrin membrane) and test group (Platelet Rich Fibrin membrane + Nanobone®). The Cone Beam Computed Tomography Fusion technique was utilized to assess crestal and horizontal bone changes after five months of the surgical procedure. Patient morbidity was recorded for one week post-surgical. Results Five months post-surgical, buccal crestal bone resorption was 1.26 ± 0.58 mm for the control group and 1.14 ± 0.63 mm for the test group. Lingual crestal bone resorption was 1.40 ± 0.66 mm for the control group and 1.47 ± 0.68 mm for the test group. Horizontal bone width gain was 1.46 ± 0.44 mm for the control group and 1.29 ± 0.73 mm for the test group. There was no significant statistical difference between study groups regarding crestal and horizontal bone changes and patient morbidity. Conclusions The tomographic assessment of NanoBone® addition in this study resulted in no statistically significant difference between study groups regarding crestal and horizontal bone changes and patient morbidity. More randomized controlled clinical trials on gap fill comparing different bone grafting materials versus no grafting should be conducted. Clinicaltrials.gov registration number NCT02836678, 13th January 2017.